Identification by cDNA cloning of abundant sRNAs in a human-avirulent Yersinia pestis strain grown under five different growth conditions. (April 2012) - Qu, Yi; Bi, Lijun; Ji, Xiaolan; Deng, Zhongliang; Zhang, Hongtai; Yan, Yanfeng; Wang, Ming; Li, Aqian; Huang, Xinxiang; Yang, Ruifu; Han, Yanping
Aims: sRNA regulation is supposedly involved in the stress response of a pathogen during infection. Yersinia pestis, the etiologic agent of plague, must encounter temperature and microenvironment changes, given its lifestyle. Here, we used the cDNA cloning approach to discover full-length sRNA candidates that are highly expressed in Y. pestis under five different growth conditions.Materials & methods: The cDNA cloning approach was improved by combining the traditional cDNA library construction with the prevalent rapid amplification of cDNA ends and RNA size selection techniques.Results: In total, 43 RNA species, including six previously annotated sRNAs, were identified. Of these, 25 sRNAs were encoded on the antisense strand of the annotated genes. Interestingly, two of these sRNAs were found on the complementary strand of noncoding RNAs. In addition, eight novel sRNAs encoded in the intergenic regions were also revealed. Ten sRNA candidates chosen for the northern blot analysis were successfully detected. Analysis of the expression patterns of 29 candidate sRNAs showed that 24 sRNAs are highly abundant in Y. pestis upon entry into the stationary growth phase.Conclusion: Our preliminary attempt at screening the novel sRNA candidates will lay the foundation for understanding the roles of sRNAs in Y. pestis physiology and pathogenesis.